BULGARIAN STUDENTS’ CONCEPTION OF THE GOOD LIFE - Stoilova, Vyara; Kineva, . Todorka (Revista Inclusiones, 2021)
The theme of the article is “the good life” as a scientific concept, a social goal and a subjective representation. The authors analyze the result of a qualitative survey conducted in February 2020 among students of the University of National and World Economy of Sofia, Bulgaria. The study aimed to identify the subjective representations of students regarding the good life they personally want to achieve, their individual efforts, and the social preconditions they consider necessary for the fulfillment of their subjective representations.